The description of Pseudobenedenia gunnari sp. n. (Monopisthocotyla: Capsalidae) from the mackerel icefish (Champsocephalus gunnari) in South Georgia Island, South Atlantic - Rubtsova, Nataliya Y. (Ukrainian Antarctic Journal, 2025)
The mackerel icefish Champsocephalus gunnari (Channichthyidae) is a highly specialised Antarctic species inhabiting cold sub-Antarctic waters, particularly around South Georgia. Although the helminth fauna of this host is relatively well documented, only one representative of Monopisthocotyla collected in 1926 during the “Discovery” expedition, later prepared as a whole mount by D. I. Gibson in the 1970s and identified as Pseudobenedenia nototheniae Johnston, 1931, has been registered so far. The present study is based on a re-examination of a museum specimen preserved in the parasitological collection of the Natural History Museum in London, United Kingdom. Standard morphological techniques were used to examine and illustrate the specimen, including analysis of key reproductive, adhesive, and haptoral structures. The new species is diagnosed by a unique combination of features, including a bilobed terminal end of penis curved anteriorly; both male and female genital ducts opening into a shared genital orifice, but at distinctly separate positions within it, and vagina not adjacent to the vitelline reservoir. An additional unique feature is an exceptionally large body size (12 mm) and proportionally larger reproductive organs. A combination of these morphological features has not been previously reported in any other Pseudobenedenia Johnston, 1931 species. Reporting this unique form of Pseudobenedenia on a new host, ecologically isolated from all previously known hosts, emphasises the novelty of our discovery. The rarity of Pseudobenedenia records on C. gunnari, despite intensive examination of the host species, underscores the difficulty of obtaining fresh material for modern morphological analyses. Distinctive features of the genital system and marked size differences provide strong evidence of reproductive isolation and support the establishment of a new Pseudobenedenia species.